The Influence Of Capital Intensity, Inventory Intensity, Size, Profitability, And Tax Avoidance On Tax Revenue In Banking Companies Listed On The Indonesia Stock Exchange - Ermadiani Ermadiani; Mukhlis Mukhlis; Abukosim Abukosim; Rina Tjandrakirana DP (International Journal of Economics, Business and Innovation Research, 2023)
This study aims to examine the effect of Tax Avoidance, Capital Intensity, ROA Net Income, Inventory Intensity, and Size on Tax Revenue. The population in this study are financial sector banking companies listed on the Indonesia Stock Exchange. The research sample was taken using a purposive sampling technique. The method of data collection is done through a literature study. The data used in this research is secondary data in the form of quantitative descriptive data. Quantitative data were obtained from the annual financial reports of financial sector banking companies obtained from the IDX for the 2016-2020 period. The analysis technique used is the classical assumption test, Chow test, Hausman test, and LM test. The results of the study show that ROA Net Income has a positive and significant effect on tax revenues.